2019
DOI: 10.1186/s13075-019-1988-6
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage endoplasmic reticulum stress may influence the onset but not the progression of experimental osteoarthritis

Abstract: Background Osteoarthritis has been associated with a plethora of pathological factors and one which has recently emerged is chondrocyte endoplasmic reticulum (ER) stress. ER stress is sensed by key ER-resident stress sensors, one of which is activating transcription factor 6 (ATF6). The purpose of this study is to determine whether increased ER stress plays a role in OA. Methods OA was induced in male wild-type (+/+), ColIITgcog (c/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…But prolonged ER stress ultimately contributed to decrease of collagen and myopia development. However, this effect of ER stress on onset and progression of FDM need to be further verified in animal models by genetic predisposition or preconditioning intervention [46]. In general, we demonstrated the characteristic of ER stress response in vitro, which established the foundation for the further study.…”
Section: Discussionmentioning
confidence: 54%
“…But prolonged ER stress ultimately contributed to decrease of collagen and myopia development. However, this effect of ER stress on onset and progression of FDM need to be further verified in animal models by genetic predisposition or preconditioning intervention [46]. In general, we demonstrated the characteristic of ER stress response in vitro, which established the foundation for the further study.…”
Section: Discussionmentioning
confidence: 54%
“…Typically, susceptibility to ER stress in the ColIITgcog mouse model has a beneficial effect. Specifically, it can mitigate OA due to the effective management of ER stress within articular chondrocytes ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…ATF6α does not contribute to the capacity of the unfolded protein response in the context of osteoarthritis Strikingly, although several studies suggested that ATF6 signalling may be responsible for the regulation of Xbp1 during OA progression, no difference in OA onset or progression could be seen in ATF6α-deficient mice after DMM surgery, suggesting that ATF6α may not be as relevant in this context as other branches of the UPR 50 . Previous studies have shown a differential expression of ATF6α and ATF6β in a cartilage growth plate and a differentiation state-dependent modulation of ATF6 signalling 16 .…”
Section: Chondrocyte Endoplasmic Reticulum Stress In Osteoarthritismentioning
confidence: 97%
“…An adapted endoplasmic reticulum stress response could delay the onset of osteoarthritis A recent study by Kung et al employed the dislocation of the medial meniscus (DMM) mouse model to study trauma-induced OA 50 . Interestingly, BiP expression was markedly increased after DMM surgery in wild-type mice, clearly demonstrating an involvement of ER stress and the UPR in the pathogenesis of OA.…”
Section: Chondrocyte Endoplasmic Reticulum Stress In Osteoarthritismentioning
confidence: 99%